Stiffness-Displacement Correlation from the RC Shear Wall Tests of the SAFE Program: Derivation of a Capacity Line Model - Francisco J. Molina; Pierre Pegon; Pierre Labbé (Advances in Materials Science and Engineering)
The response of 13 reinforced concrete shear walls submitted to successive seismic tests has been postprocessed to produce time histories of secant stiffness and displacement oscillation amplitude. For every wall an envelope curve of displacement amplitude versus stiffness is identified which is fairly modelled by a straight line in double logarithmic scale. This relatively simple model, when used as a capacity line in combination with the demand response spectrum, is able to predict in an approximate manner the maximum response to the applied earthquakes. Moreover, the graphic representation of the demand spectrum and a unique model capacity line for a group of equal walls with different assumed design frequencies on them gives a visual interpretation of the different safety margins observed in the experiments for the respective walls. The same method allows as well constructing vulnerability curves for any design frequency or spectrum. Finally, the comparison of the different identified line models for the different walls allows us to assess the qualitative effect on the behaviour of parameters such as the reinforcement density or the added normal load.